Pengaruh Variasi Menu, Service Quality, dan Lokasi terhadap Keputusan Pembelian pada Ramen Master cabang Merr Surabaya - Cahyaningthyas, Afifa Devi; Abdul Halik (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This research aims to test and analyze the influence of menu variations, Service Quality and location on consumer purchasing decisions at Ramen Master Merr Branch Surabaya. This research uses quantitative methods with a survey approach. The sample used was 100 respondents who had purchased Ramen Master at the Merr Surabaya branch. Data collected through a questionnaire with a Likert Scale as a measurement instrument. Data analysis techniques were carried out using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, as well as t tests (partial) and F tests (simultaneous) to evaluate the effect of Menu Variations, Service Quality. And Location on Purchasing Decisions.The results of this research show that all indicators are valid and reliable. Based on the Multiple Linear Regression test, the Menu Variation variable has a more dominant influence, while the Location variable has a lower influence. The results of the t test state that Menu Variation partially has a significant influence on purchasing decisions, Service Quality partially has a significant influence on purchasing decisions, and Location partially has an influence but is not significant on purchasing decisions at Ramen Master Merr Surabaya branch. The F test states that Menu Variation, Service Quality and Location simultaneously have a significant influence on Purchasing Decisions at Ramen Master Merr Surabaya branch. Meanwhile, the results of the Coefficient of Determination (R2) test show that the influence of the independent variable on the dependent variable is 71.9%, while the remaining 28.1% is influenced by other variables outside the research model. Keywords: Menu Variations, Service Quality, Location and Purchasing Decisions